HIV-Related Sexual Risk Among Transgender Men Who Are Gay, Bisexual, or Have Sex With Men. (1st April 2017) - Scheim, Ayden I.; Bauer, Greta R.; Travers, Robb
Abstract : Background: This study is among the first to examine factors associated with HIV-related sexual risk among transgender men and other transmasculine persons who are gay, bisexual, or have sex with men (T-GBMSM). Methods: In 2009–2010, 433 transgender people in Ontario, Canada, participated in a multimode respondent-driven sampling survey, including 158 T-GBMSM. Analyses were weighted using respondent-driven sampling II methods to adjust for differential recruitment probabilities; confidence intervals (CI) were adjusted for clustering by shared recruiter. Prevalence ratios (PR) for associations with past-year high sexual risk (condomless intercourse outside a seroconcordant monogamous relationship) were estimated using average marginal predictions from logistic regression. Results: Of T-GBMSM (mean age = 29.8; 52% living full time in felt gender; 25% Aboriginal or persons of color; 0% self-reported HIV positive), 10% had high sexual risk activity in the past year. Among the 34% with a past-year cisgender (non-transgender) male sex partner, 29% had high sexual risk. In multivariable analyses, older age, childhood sexual abuse (adjusted PR, APR = 14.03, 95% CI: 2.32 to 84.70), living full time in one's felt gender (APR = 5.20, 95% CI: 1.11 to 24.33), and being primarily or exclusively attracted to men (APR = 5.54, 95% CI: 2.27 to 13.54) were each associated with sexual risk. Of psychosocial factors examined, past-year stimulant use (APR = 4.02, 95% CI: 1.31 to 12.30) and moderate depressive symptoms (APR = 5.77, 95% CI: 1.14 to 29.25) were associated with higher sexual risk. Conclusions: T-GBMSM seem to share some HIV acquisition risk factors with their cisgender counterparts. HIV prevention interventions targeting T-GBMSM who are predominantly attracted to men and interventions addressing sequelae of childhood sexual abuse may be warranted.